THU0253 A Polymorphism Upstream MIR1279 Gene Is Associated with Pericarditis in Systemic Lupus Erythematosus and Contributes To Definition of A Genetic Risk Model Profile. (15th July 2016) - Perricone, C.; Ciccacci, C.; Ceccarelli, F.; Cipriano, E.; Rufini, S.; Politi, C.; Latini, A.; Alessandri, C.; Spinelli, F.R.; Novelli, G.; Valesini, G.; Borgiani, P.; et al.
Abstract : Background: MicroRNAs have emerged as important regulators of gene expression in post-transcriptional level. These are a class of small non-coding molecules, which could contribute to the pathogenesis of autoimmune diseases, including systemic lupus erythematosus (SLE). Recently, it has been demonstrated that the rs1463335 SNP in MIR1279 gene region was associated with decreased levels of TRAF3IP2 expression. We have previously demonstrated an association between TRAF3IP2 polymorphisms and SLE, especially with the development of pericarditis (1). Objectives: Thus, we aimed to investigate the role of the MIR1279 rs1463335 SNP in SLE, with particular regards to pericarditis development. Furthermore, we aimed at constructing a pericarditis genetic risk profile for SLE patients considering others risk alleles that we had previously found associated with pericarditis development (1, 2). Methods: We recruited 315 Italian SLE patients and 278 healthy controls. Rs1463335 SNP, located upstream MIR1279 gene, was analyzed by allelic discrimination assay. MIR1279 gene was further sequenced in 50 patients. Genotyping of rs7574865 (STAT4), rs2542151 (PTPN2), rs2241880 (ATG16L1) and rs33980500 (TRAF3IP2) SNPs were also performed. A case/control association study and a genotype/phenotype correlation analysis were performed and a risk profile model for pericarditis in SLE was built. Results: The full sequencing of the MIR1279 gene in SLE patients did not reveal any novel or known variation. The variant allele of the rs1463335 SNP was significantly associated with susceptibility to pericarditis (P=0.017, OR=1.67). Patients carrying the A allele were more susceptible to develop the pericarditis with an allele-additive effect: patients carrying the variant homozygous genotype have a higher risk than patients carrying the heterozygous genotype (P=0.013, OR=3.28 vs P=0.06, OR=2.4, respectively). A risk profile model for pericarditis considering the risk alleles of MIR1279 and other three genes (STAT4, PTPN2 and TRAF3IP2) showed that patients with 4 or 5 risk alleles have a significantly higher risk to develop pericarditis (OR=4.09 with P=0.001 and OR=6.04 with P=0.04 respectively). Anti-Sm antibodies were the only parameter associated with the development of pericarditis. A multivariate analysis by binary regression analysis, considering as dependent variable the presence/absence of pericarditis and as independent variables all the studied SNPs associated with pericarditis, was performed. In a stepwise approach including anti-Sm, MIR1279, STAT4, TRAF3IP2 and PTPN2 SNPs, this model explains about 25% (R 2 Cox &Snell) of the variability involved in the susceptibility to pericarditis. Conclusions: We describe for the first time the contribution of a MIR1279 SNP in pericarditis development in SLE patients and a genetic risk profile model useful to identify patients more susceptible to develop pericarditis in SLE. This approach could help to improve the prediction and the management of this manifestation. References: Perricone C, et al. Immunogenetics. 2013 Oct;65(10):703–9. Ciccacci C, et al. PLoS One. 2014 Nov 4;9(11):e111991. Disclosure of Interest: None declared